Cephalometric characteristics of postorthodontic female patients with attractive and unattractive frontal posed smiles - Kawashima, Yuka (Angle Orthod, 2018)
OBJECTIVES: To identify differences in skeletal, dental, and soft-tissue morphology between postorthodontic patients with attractive and unattractive frontal posed smiles. MATERIALS AND METHODS: The attractiveness of close-up photographs of frontal posed smiles in 100 adult female patients after conventional orthodontic treatment was evaluated by 20 dental students (10 men, 10 women) using a visual analogue scale. Posttreatment cephalograms of the 20 patients with the most attractive smiles (attractive group; mean age 23.75 ± 3.35 years) and the 20 patients with least attractive smiles (unattractive group; mean age 23.11 ± 4.45 years) were selected, and 41 measurements were made and compared between groups using the Mann-Whitney U-test (P < .05). RESULTS: When compared with the attractive group, the unattractive group exhibited greater values for sella-nasion plane to mandibular plane, palatal plane to mandibular plane, anterior facial height, lower facial height, and lower facial height/anterior facial height as skeletal measurements; for occlusal plane to sella-nasion plane, palatal plane to occlusal plane, and maxillary central incisor to palatal plane as dental measurements; and for lower face, upper lip length, and upper lip superior to palatal plane as soft-tissue measurements. CONCLUSIONS: Cephalometric analysis revealed that postorthodontic Japanese female patients with unattractive frontal posed smiles are characterized by a hyperdivergent skeletal pattern with extruded maxillary incisors and a steep occlusal plane, accompanied by a longer upper lip than patients achieving attractive posed frontal smiles.